2023
DOI: 10.1108/ijse-11-2022-0766
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of public spending for agricultural development in India: a disaggregate analysis contextualizing subsidies vs investment debate

Abstract: PurposeThe primary objective of the present study is to figure out the relative effectiveness of alternate public expenditure with regard to agricultural development particularly in the context of input subsidies vis-a-vis investment. Besides, the authors also endeavour to test the applicability of crowding-out hypothesis in the present context.Design/methodology/approachInitially, unit root tests are applied for checking stationarity of the underlying data using Augmented Dickey-Fuller (ADF) and Kwiatkowski–P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Gautam [41] illustrated that in countries where subsidies are a major contributor to public spending, the effect on agricultural growth is negative. The study conducted by Zafar and Tarique [42] showed that public investment is a better alternative for agricultural development compared to subsidies. The analysis by Baig et al [43] on the effect of agricultural subsidies on agricultural productivity stated that the governmental focus should be on technological innovations in the agricultural sector to promote growth and development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gautam [41] illustrated that in countries where subsidies are a major contributor to public spending, the effect on agricultural growth is negative. The study conducted by Zafar and Tarique [42] showed that public investment is a better alternative for agricultural development compared to subsidies. The analysis by Baig et al [43] on the effect of agricultural subsidies on agricultural productivity stated that the governmental focus should be on technological innovations in the agricultural sector to promote growth and development.…”
Section: Literature Reviewmentioning
confidence: 99%